Kelimpahan dan Pola Keberadaan Lalat Buah (Diptera: Tephritidae) pada Pertanaman Monokultur dan Polikultur di Kabupaten Kotawaringin Timur - Benvica Regita Cahyani; Helda Orbani Rosa (JURNAL PROTEKSI TANAMAN TROPIKA, 2026)
Fruit flies (Diptera: Tephritidae) are a major pest of horticultural crops, causing fruit to rot and fall before harvest. This study aimed to determine the abundance and patterns of fruit fly occurrence using methyl eugenol (ME) traps in monoculture and polyculture cropping systems in East Kotawaringin Regency. The method used was a survey using thepurposive random sampling at three different locations for each type of crop. The captured fruit flies were identified based on morphology, such as wing pattern and shape, and the color of the head, thorax, legs, and abdomen. The results showed that two species were found in monoculture land: Bactrocera dorsalis And B. umbrosawith a diversity index of 0.096–0.220 and a species richness index of 0.160–0.253. Three species were identified in the polyculture area, namely B. dorsalis, B. occipitalis, And B. umbrosa, with diversity values ​​of 0.531–0.828 and species richness of 0.300–0.350. The dominance index at all locations had a value of one indicating strong dominance by B. dorsalis cropping patterns and environmental factors such as pesticide use intensity and changes in land use also influence the composition and abundance of fruit fly populations. These findings form the basis for ecologically based pest management.